Heat‐stress Memory is Responsible for Acquired Thermotolerance in Bangia fuscopurpurea. Issue 5 (8th October 2019) - Kishimoto, Ikuya; Ariga, Inori; Itabashi, Yutaka; Mikami, Koji
Abstract : The environmental stresses that sessile organisms experience usually fluctuate dramatically and are often recurrent. Terrestrial plants can acquire memory of exposure to sublethal heat stress to acquire thermotolerance and survive subsequent lethal high‐temperature stress; however, little is known concerning whether seaweeds acquire thermotolerance via heat‐stress memory. We have demonstrated that the red seaweed Bangia fuscopurpurea can indeed acquire memory of sublethal high‐temperature stress, resulting in the acquisition of thermotolerance that protects against subsequent lethal high‐temperature stress. Moreover, the maintenance of heat‐stress memory was associated with a slight increase in the saturation level of membrane fatty acids. This suggests that the modification of membrane fluidity via changes in membrane fatty acid composition is involved in the establishment and maintenance of heat‐stress memory in B. fuscopurpurea . These findings provide insights into the physiological survival and growth strategies of sessile red seaweeds to cope with recurrent changes in environmental conditions.